Negotiated Re-orienting: A Theory Generated through International Collaborative Research - Tom Andrews (Grounded Theory Review: An International Journal)
The theory presented here was generated from a research project that involved researchers in five countries. To our knowledge, this is the first classic grounded theory generated by such an international collaborative effort. This article starts by describing the collaborative process, then the theory is presented.